The effect of M-phase stage-dependent kinase inhibitors on inositol 1,4,5-trisphosphate receptor 1 (IP3R1) expression and localization in pig oocytes - Anucha Sathanawongs (2018)
© 2014 Japanese Society of Animal Science. At fertilization, inositol 1,4,5-trisphosphate receptor type 1 (IP 3 R1) has a crucial role in Ca 2+ release in mammals. Expression levels, localization and phosphorylation of IP 3 R1 are important for its function, but it still remains unclear which molecule(s) regulates IP 3 R1 behavior in pig oocytes. We examined whether there was a difference in localization of IP 3 R1 after in vitro or in vivo maturation of pig oocytes. In mouse oocytes, large clusters of IP 3 R1 were formed in the cortex of the oocyte except in a ring-shaped band of cortex adjacent to the spindle. However, no such clusters of IP 3 R1 were observed in pig oocytes and there was no difference in its localization between in vitro and in vivo matured oocytes. We next tried to clarify which factor(s) regulates IP 3 R1 localization, phosphorylation and expression using M-phase stage-dependent kinase inhibitors. Our results show that treatments with roscovitine (p34 cdc2 kinase inhibitor) or U0126 (mitogen-activated protein kinase inhibitor) did not affect IP 3 R1 expression or localization in pig oocytes, although the latter strongly inhibited phosphorylation. However, treatment with BI-2536, an inhibitor of polo-like kinase 1 (Plk1), dramatically decreased the expression level of IP 3 R1 in pig oocytes in a dose-dependent manner. From these results, it is suggested that Plk1 is involved in the regulation of IP 3 R1 expression in pig oocytes.